Opinions of Kazakhs in Russian territory on monuments to sacred geography (The Journal of Psychology and Sociology, 2022)
To form the Kazakh people shrines cultural and geographical belt, it is very important searching and study sacred objects and significant places associated with Kazakh historical figures abroad. Article analyzes the border Kazakhs level of interest of to sacred monuments of the Kazakh people in Russia, as well as the holy places role in their lives, and sources of their knowledge about sacred objects. The article is based on field expedition materials of from 4 regions of Russia bordering Kazakhstan, processed using quantitative and qualitative methods.The paper presents results of the quota-territorial sample so- ciological survey of Kazakhs, conducted in August 2021 in the Astrakhan, Volgograd, Saratov, Orenburg regions.The importance of the study makes a case to determine directions and work content to disseminate knowledge about the Kazakhs spiritual shrines of among population and, foremost, young people in order to contribute to formation of the national identity framework.As a conceptual approach, there are used ideas about working with memory as a way of “connecting”, but not just reproducing existing relationships.Observations and conclusions, proposed conceptual approach and results of the study can further deepen theoretical and empirical developments on this issue.Key words: sacred geography, shrines, Russian Kazakhs, monuments, mausoleums, cultural heritage.